Real word outcomes of cabozantinib therapy in poorly differentiated thyroid carcinoma - Omar Elghawy; Adam Barsouk; Jessica Xu; Simon Chen; Roger B Cohen; Lova Sun (European Thyroid Journal)
Objective: Poorly differentiated thyroid carcinomas (PDTCs) are rare and aggressive head and neck malignancies with a poor prognosis. Systemic treatment for incurable PDTC consists of multi-kinase inhibitors (MKIs) based on extrapolation from the experience with radioiodine refractory differentiated thyroid cancer (DTC). Cabozantinib is an approved second-line MKI therapy for DTC, but there are limited data regarding the safety and efficacy of cabozantinib for PDTC. Methods: We conducted a single-institution, retrospective analysis of patients with PDTC who received cabozantinib in any line of therapy. Baseline demographics, disease characteristics, treatment history, toxicity, and clinical outcomes were abstracted from the electronic medical record. Median progression-free survival (PFS) and overall survival (OS) were primary endpoints and estimated using Kaplan–Meier methodology. Results: Seven patients with PDTC who received cabozantinib were included. 4/7 (57%) patients had a partial response to cabozantinib, while 2/7 (29%) had stable disease (SD) as their best response. The median time on treatment for cabozantinib was 10.53 months. The median PFS from the start of cabozantinib was 12.9 months, and median OS was 14.21 months. Most adverse events to treatment (5/6) were low grade. Two (29%) patients were alive at the date of the last follow-up. Conclusion: Cabozantinib is an effective and reasonably well-tolerated treatment option for patients with PDTC. Prospective studies are needed to further investigate the role of cabozantinib in the treatment of PDTC, alone and in combination with other agents, including checkpoint inhibitors.